SOYBEAN VARIETIES DIFFER IN THE VELOCITY AND CAPACITY OF WATER ABSORPTION - COSTA, José Antonio; PIRES, João Leonardo Fernandes; THOMAS, André Luis; ALBERTON, Marilac (Scientia Agraria, 2002)
The seeds resume the metabolic process by imbibition, which supplies the necessity of water and promote the beginning of germination. The present study, performed at the Faculdade de Agronomia of Universidade Federal do Rio Grande do Sul, Porto Alegre, RS, in the 1993 year, was undertaken to evaluate the behavior of soybean cultivars in relation to maximum capacity and velocity of water absorption, measured in hourly intervals, for eight consecutive hours, in total imbibition in water. Seeds of 17 cultivars with diameter larger than 6.3 mm and with absence of cracks when observed with binocular in the seed coat were utilized. The cultivar RS 6 Guassupí showed the highest velocity and capacity of water absorption. FT Abyara and Bragg showed the smallest velocity and capacity of water absorption in the first hours of imbibition, but in the last hours RS 7 Jacuí was the one which presented the smallest water absorption capacity. The conclusion from this study is that the cultivars tested have some distinct caracteristic that allowed for the diferences in the water imbibition velocity and total capacity of water absorption that was not detected in this research.